(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2019)
This study was conducted to explore the possibility of substitution of wheat flour with 10%, 20%, 30%, 35% and 40% buckwheat (Fagopyrum esculentum) flour and to formulate bread with improved nutritional value along with acceptable nutritional and sensory attributes, and to compare with locally available breads. The results showed that the ash (0.80-1.21%), protein (10.11-16.23%), fat (4.88-5.85%), fiber (0.07-0.19%), energy (301-322 kcal/100g) and mineral contents were increased with the increasing content of buckwheat flour in the bread preparation. Physical characteristics were decreased with the increasing content of buckwheat flour. On sensory evaluation, bread formulated with 30% buckwheat flour was found acceptable. In comparison with locally available breads, 30% buckwheat flour substituted bread was found significantly higher in ash, protein, fiber and energy content. Based on these results, it can be concluded that bread prepared with 30% substitution of wheat flour with buckwheat flour is nutritionally superior over locally available breads. Bangladesh J. Sci. Ind. Res.54(4), 347-356, 2019